The Accounting Based Valuation of Corporate R&D - Sougiannis, Theodore (The Accounting Review, 1994)
[This article examines whether reported accounting earnings reflect benefits from past research and development (R&D) expenditures and uses the benefits, if any, to estimate the investment value of R&D. The issue is how to extract realized R&D benefits from income statement numbers and is important given the current accounting policy of expensing R&D as incurred. To the extent that market participants can determine realized benefits and expect these benefits to persist in the future, they will use accounting earnings numbers to value current R&D. This study uses cross-sectional data to estimate a recursive system of two equations: one for earnings and one for valuation. The earnings equation associates earnings with recorded assets, advertising, and R&D expenditures. It extracts realized R&D benefits from reported earnings numbers. The valuation equation relates market values of equity to book values, earnings, and R&D expenditures. It determines how the accounting and R&D numbers are valued in the market. The coefficients derived from these two equations are then used to estimate the investment value of R&D. This system of equations assumes that past R&D generates earnings that create market value. The results from the earnings model indicate that reported earnings, adjusted for the expensing of R&D, do reflect realized benefits from R&D. On average, a one-dollar increase in R&D expenditures leads to a two-dollar increase in profit over a seven-year period. The results from the valuation model indicate that investors place a high value on R&D investments. On average, a one-dollar increase in R&D expenditure produces a five-dollar increase in market value. This effect of R&D on market values can be separated into an indirect and a direct component. The indirect effect, when R&D outlays affect market values through earnings, is the capitalized value of R&D benefits reflected in earnings and expected to persist, given that R&D is continuous. In contrast, the direct effect reflects new R&D information conveyed directly by R&D variables. On average, the indirect effect is much larger than the direct effect, implying that R&D information conveyed by earnings numbers is more valued than the information conveyed by the R&D variables themselves. Finally, the study controls for the valuation of R&D tax shields generated when firms expense R&D for tax purposes, and/or qualify for the R&D tax credit. The tax shields are found to be relevant and are valued as earnings.]